1996
DOI: 10.1007/bf02338799
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the RH locus in gorillas and chimpanzees

Abstract: The human Rh blood-group system is encoded by two homologous genes, RhD and RhCE. The RH genes in gorillas and chimpanzees were investigated to delineate the phylogeny of the human RH genes. Southern blot analysis with an exon 7-specific probe suggested that gorillas have more than two RH genes, as has recently been reported for chimpanzees. Exon 7 was well conserved between humans, gorillas, and chimpanzees, although the exon 7 nucleotide sequences from gorillas were more similar to the human D gene, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The nucleotide sequence of intron 4 in the RHD gene was entirely consistent with that reported by Huang. Comparing our data with the report of Westhoff et al (25), however, there are many nucleotide differences: two deletions (G at nucleotide 1, A at nucleotide 316), a single insertion (G next to nucleotide 426) in intron 4 of the RHD gene, four deletions (G at nucleotide 1, G at nucleotide 545, C at nucleotide 953, A at nucleotide 965), four insertions (G at nucleotide 308, A at nucleotide 409, G at nucleotide 414, G next to nucleotide 1075), and three substitutions (C→T at nucleotide 308, A→G at nucleotide 685, G→A at nucleotide 799) in intron 4 of the RHCE gene (Fig. 2).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The nucleotide sequence of intron 4 in the RHD gene was entirely consistent with that reported by Huang. Comparing our data with the report of Westhoff et al (25), however, there are many nucleotide differences: two deletions (G at nucleotide 1, A at nucleotide 316), a single insertion (G next to nucleotide 426) in intron 4 of the RHD gene, four deletions (G at nucleotide 1, G at nucleotide 545, C at nucleotide 953, A at nucleotide 965), four insertions (G at nucleotide 308, A at nucleotide 409, G at nucleotide 414, G next to nucleotide 1075), and three substitutions (C→T at nucleotide 308, A→G at nucleotide 685, G→A at nucleotide 799) in intron 4 of the RHCE gene (Fig. 2).…”
Section: Resultssupporting
confidence: 84%
“…Huang showed all sequences of intron 4 in the RHD gene, and indicated the existence of the human Alu repeat in intron 4 of the RHCE gene (24). Westhoff et al demonstrated the Alu element similar to Huang's report in addition to all sequences of intron 4 in both the RHD and RHCE genes (25). To identify intron 4 of the RHD gene and the RHCE genes, we carried out the PCR amplification with primers F3/R3.…”
Section: Resultsmentioning
confidence: 61%
“…In red and green opsin genes, several polymorphic amino acids are shared by these paralogous loci in each of humans, chimpanzees and gorillas, suggesting frequent gene exchanges between the loci (Deeb et al 1994). Similarly, for the Rh locus, frequent gene exchanges between D and CE genes were reported (Westhoff and Wylie 1996). These sequence exchanges between loci either increase or decrease the extent of the neutral variation, depending on the size of the transferred segments (Ohta 1982).…”
Section: Isozyme Electrophoretic Datamentioning
confidence: 98%
“…Other polymorphism data Some other polymorphic loci have been examined at the nucleotide sequence level in humans and chimpanzees/gorillas: genes for pyruvate dehydrogenase E1 α subunit (PDHA1; Harris and Hey a: L = the number of loci examined, P = the number of polymorphic loci, H = the average heterozygosity b: n = the number of samples 1999), red and green opsins (Deeb et al 1994), Rh blood type (Rh; Westhoff and Wylie 1996), protamine 1 and 2 (Pr1 and Pr2) (Wyckoff et al 2000), and major histocompatibility complex (Mhc) ( e.g., de Groot et al 2000). At the PDHA1 locus the nucleotide diversity of 36 human and two chimpanzee DNA sequences were examined.…”
Section: Isozyme Electrophoretic Datamentioning
confidence: 99%
“…Both RHCE and RHD have ten exons and the mRNA sequence identity between them was found to be about 96 % Le Van Kim et al, 1992;Cherif-Zahar et al, 1994). A distinct difference between these two genes lies in the length of intron 4; intron 4 of RHCE is about 650 bp longer than that of RHD due to Alu sequence insertion (Westhoff and Wylie, 1996;Huang 1997;Okuda et al, 1997). Recently, the DNA sequence homology between the two RH genes including all exons and introns was reported to be 91.7 % (Okuda et al, 2000).…”
mentioning
confidence: 99%